2016
DOI: 10.1080/00207543.2016.1193252
|View full text |Cite
|
Sign up to set email alerts
|

Strategic ramp-up planning in automotive production networks

Abstract: In many industries, the frequency of production ramp-ups has increased due to shorter product life cycles and increased product variety. Production often takes place at globally dispersed facilities for customers in multiple markets, for example, in the automotive industry. Therefore, ramp-up planning must be carried out for a network. The planning problem at hand is to simultaneously optimise the allocation of products of a common product platform to plants, the timing of ramp-ups and ramp-downs, ramp-up dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Research has been reported from Germany (e.g. Glock and Grosse, 2015;Wochner et al, 2016;Becker et al, 2017) and UK (e.g. Doltsinis et al, 2013) that has mainly been concerned with decision support tools to plan and control the production ramp-up at the OEM.…”
Section: Conclusion and Implications 61 Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has been reported from Germany (e.g. Glock and Grosse, 2015;Wochner et al, 2016;Becker et al, 2017) and UK (e.g. Doltsinis et al, 2013) that has mainly been concerned with decision support tools to plan and control the production ramp-up at the OEM.…”
Section: Conclusion and Implications 61 Theoretical Implicationsmentioning
confidence: 99%
“…The pace at which companies innovate has accelerated in recent years as product life cycles have drastically decreased (Li et al, 2014;Hansen and Grunow, 2015;Becker et al, 2017). This indicates that the time from the start of production (SOP) until the products are withdrawn from the market has decreased; hence, companies have less time to make profits by: focusing on the need to integrate suppliers in NPD to manage production ramp-up of a new product.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the model diversity of AUDI AG increased significantly, from three models in 1980 to more than 17 models by 2025 (Gesell et al , 2018; Jung, 2017). Shorter product life cycles as well as increased product variety due to customization and new technologies, lead to more ramp-up processes (Becker et al , 2017; Schmitt et al , 2018; Valpato and Stocchetti, 2008; Wochner et al , 2016). In view of the increased number of ramp-ups, it is problematic that according to Bauer et al (2014, p. 421) “50% of all series ramp-ups do not reach their technical targets and 33% do not reach their commercial targets.”…”
Section: Introductionmentioning
confidence: 99%
“…Surbier et al (2014) showed in their overview on production ramp-up that since the late 1990s the topic has gained more and more research interest. Today, the literature about production ramp-up is heterogeneous and addresses topics, such as planning (Becker et al , 2017; Bohn and Terwiesch, 1999; Winkler et al , 2007), knowledge management (Fjällström et al , 2009; Yeleneva et al , 2018), personnel management (Säfsten et al , 2008) and product development, as well as change management (Schuh et al , 2017). However, it seems as if the role of the procurement department has not been in the center of the studies nor the opportunities provided by improved buyer–supplier communication.…”
Section: Introductionmentioning
confidence: 99%
“…On a network scale, Becker et al considered a strategic ramp-up planning process for automotive production networks. They utilised a hierarchical planning framework to strategically determine ramp up and down decisions, and show that their strategic ramp up planning model outperforms sequential planning approaches (Becker, Stolletz, & Stäblein, 2017).…”
Section: Transition and Ramp Up Production Structuresmentioning
confidence: 99%